Konsep Matematika dalam Kearifan Lokal Arsitektur Rumah Adat Batak Toba - Anggi Brigita Cesaria Saragih; Elvi Mailani; Erika Juliani Purba; Fanny Tio Anderesta Siahaan; Laurencia Stephanie Gregoria Purba; Rika Silalahi; Yosep Lamtama Tampubolon; Nur Rarastika (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study aims to examine the application of mathematical concepts, such as proportion, and symmetry, in traditional Batak house architecture through an ethnomathematics approach. The method used is a literature study, where data is obtained from various written sources, such as books, scientific journals, and related articles. The analysis was carried out by content analysis, namely by identifying and categorizing the main themes that appear in the literature, then synthesized to understand how Batak local wisdom reflects the application of mathematical concepts in the design and construction of traditional houses, especially Bolon houses. The results of the study indicate that the Batak people traditionally apply mathematical principles in creating strong, aesthetic, and symbolic building structures, and are relevant to their cultural values. This study reveals that the concept of ethnomathematics plays an important role in understanding the relationship between mathematics and local culture.